Modernization of economy of Omsk Region: contribution of Omsk State Technical University - O. P. Kuznetsova; E. A. Yumaev; S. V. Kuznetsova; N. I. Tishchenko (Омский научный вестник: Серия "Общество. История. Современность")
The article presents key directions where the University has achieved notable successes in motivating pupils and students to master engineering specialties. Based on the results of the study, one suggested developing professional trainings for engineering students, launching the «Omsk Irtysh Land Personnel Reserve» information system. As a result of the proposed activities implementation, the Omsk State Technical University will increase the demand for its graduates in the labor market, promote the development of high-tech industry in the Omsk region and beyond, strengthen its position in the educational services market and raise the level of its brand recognition in Russia and abroad. Suggestions developed on the basis of the regional flagship Omsk State Technical University experience are of a universal nature and can be used in higher educational institutions that carry out training in engineering specialties